Treatable massive pericardial effusion and hypertrophic cardiomyopathy in an infant with a novel homozygous ACADVL mutation: A case report. Issue 20 (May 2018) - Kim, Yoo-Mi; Kim, Geena; Ko, Hoon; Yoo, Han-Wook; Lee, Hyoung Doo
Abstract: Rationale: Infantile-onset hypertrophic cardiomyopathy (HCMP) should be considered a largely genetic condition, although its onset is most often triggered by infection. Very long chain acyl-CoA dehydrogenase (VLCAD) deficiency is a rare autosomal recessive inborn error of mitochondrial fatty acid β-oxidation that often causes severe cardiomyopathy and/or sudden death during the neonatal period. Patient concerns: Herein, we report an infant with VLCAD deficiency who presented with severe cardiac manifestations, including massive pericardial effusion and HCMP. The subject's older sister died of unknown causes at three days of age; however, the subject exhibited a normal tandem mass-spectrometry profile during the neonatal period. Diagnoses: During her later cardiac presentation, the subject's C-14 and C-18 levels became elevated, and she was determined, via the conducted molecular analysis, to harbor a novel homozygous frameshift mutation (c.103_112dup) in ACADVL. Interventions: After VLCAD deficiency diagnosis, the subject was treated with the administration of a medium chain triglyceride formula and fluid therapy. Outcomes: The subject's cardiac status was markedly improved by the dietary intervention and fluid therapy. Lessons: This report highlights that genetic mutations should be investigated as possible causes of infantile-onset HCMP, and that early diagnosis and intervention can prevent mortality for patients with VLCAD deficiency.